Mechanism of hot electron electroluminescence in GaN-based transistors. (29th September 2016) - Brazzini, Tommaso; Sun, Huarui; Sarti, Francesco; Pomeroy, James W; Hodges, Chris; Gurioli, Massimo; Vinattieri, Anna; Uren, Michael J; Kuball, Martin
Abstract: The nature of hot electron electroluminescence (EL) in AlGaN/GaN high electron mobility transistors is studied and attributed to Bremsstrahlung. The spectral distribution has been corrected, for the first time, for interference effects due to the multilayered device structure, and this was shown to be crucial for the correct interpretation of the data, avoiding artefacts in the spectrum and misinterpretation of the results. An analytical expression for the spectral distribution of emitted light is derived assuming Bremsstrahlung as the only origin and compared to the simplified exponential model for the high energy tail commonly used for electron temperature extraction: the electron temperature obtained results about 20% lower compared to the approximated exponential model. Comparison of EL intensity for devices from different wafers illustrated the dependence of EL intensity on the material quality. The polarization of electroluminescence also confirms Bremsstrahlung as the dominant origin of the light emitted, ruling out other possible main mechanisms.